Piloting a community rangeland health workers system within a One Health approach to strengthen pastoral extension services - Ebro, Abule; Sircely, Jason A; Eba, Bedasa; Mor, Siobhan M; Belay, K.; Admasu, B.; Fascendini, M.; Said, Mohammed; Guyo, Golicha; Abdi, Hamse; Flintan, Fiona E. (International Livestock Research Institute, 2025)
The project HEAL (One Health Units for Human, Animal, Environment and Livelihoods) is establishing One Health delivery at local level in pastoral areas of Ethiopia, Kenya and Somalia. ILRI is piloting the establishment of a local-level driven community rangeland health system including community rangeland health workers.